Changes in rice kernel and starch during parboiling process - Sittipod, Sichaya (Kansas State University, 2014)
The objective of this study was to systematically understand the changes of rice during the parboiling process. Isolated rice starch, milled rice and paddy rice kernels of the same variety (18% amylose) were examined after steeping at temperatures (60-75 oC) below and above the onset of rice starch gelatinization temperature for different durations in 66.7% water. Changes in gelatinization temperatures were greater for isolated starch ˃> milled rice ˃ paddy rice. Annealing above samples’ original To caused partial gelatinization, loss of crystallinity, and birefringence as determined by X-ray diffraction (XRD), differential scanning calorimetry (DSC), and light microscopy. However, starch granules in milled rice and paddy rice, which were surrounded by non-starch components, maintained their granule integrity. Scanning electron microscopy (SEM) revealed morphological differences between starch granules within native and steeped rice kernels. Steeped kernels had denser structures than native kernels, as determined by high resolution X-ray microtomography. Rice starch granules and kernel characteristics were altered significantly during steeping and changes in isolated starch differed from those inside the rice kernels. To study the changes during the steaming process, the morphology of the rice kernel and starch granules within the kernel were examined immediately after heating at110oC for 20 min. Starch was completely gelatinized as determined by DSC and XRD, indicating the disruption of all short-range crystallinity of starch in parboiled rice. However, SEM showed intact starch granules and light microscopic images showed starch granules embedded in the rice kernel. Interestingly, these granules displayed Maltese cross patterns. For the first time, we demonstrated that starch granules were birefringent and showed the Maltese cross but were not crystalline.
Keywords: Parboiling; Annealing; Rice; Agriculture, General (0473)